2015
DOI: 10.2355/isijinternational.55.1157
|View full text |Cite
|
Sign up to set email alerts
|

DRI from Recycled Iron Bearing Wastes for Lower Carbon in the Blast Furnace

Abstract: Reduction of Fe-bearing FINEX process waste and carbon composite pellets from 1 373 K to 1 573 K to produce DRI (direct reduced iron) for use in the blast furnace was investigated using a modified thermogravimetric analyzer. Reduction from the initial Fe 2 O 3 was not uniform throughout the composite pellet. Oxygen removal from the Fe 2 O 3 rich composite pellets over 84% was only observed at 1 573 K. Lower temperatures resulted in significantly un-reduced FeO t due to the premature consumption of the carbon. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Therefore, heat requirement in zone‐II is calculated from sensible heat required to heat the coal char and iron ore from 400 to 900 °C. Reduction reaction (Equation and 10) at 900 °C carried out in zone‐III, which is highly endothermic in nature and after reduction the reaction product consist of metallic iron, iron in combined form, and gangue. Finally, the reaction product is heated to solid exit temperature (1250 °C for the present study) from 900 °C.…”
Section: Model Predictions (Co2 Emission) For Sponge Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, heat requirement in zone‐II is calculated from sensible heat required to heat the coal char and iron ore from 400 to 900 °C. Reduction reaction (Equation and 10) at 900 °C carried out in zone‐III, which is highly endothermic in nature and after reduction the reaction product consist of metallic iron, iron in combined form, and gangue. Finally, the reaction product is heated to solid exit temperature (1250 °C for the present study) from 900 °C.…”
Section: Model Predictions (Co2 Emission) For Sponge Processesmentioning
confidence: 99%
“…There has been extensive work performed on the reduction of iron ore-coal composite pellets and its kinetics in RHF experimentally as well as mathematical modeling. [3][4][5][6][7][8][9][10][11][12][13] But only few work has been reported on modeling of RHF for arriving at energy requirements and CO 2 emission (kg-CO 2 /ton product iron) of RHF process routes like Fastmelt and ITmk3. It is reported that energy consumptions and emissions of CO 2 from RHF are lower than in the blast furnace route.…”
Section: Introductionmentioning
confidence: 99%
“…The production of RHF is affected, because the occurrence of deposition reduces the heat transfer efficiency and increases the furnace pressure. In the past, regarding the RHF process study, researchers were often concerned about the metal element reduction and energy efficiency [8][9][10][11][12], while the effect of deposition on the heat transfer system for RHF was ignored. In this study, the deposition was…”
Section: Introductionmentioning
confidence: 99%
“…Commercial plants of coal‐based rotary hearth furnace (RHF) have achieved some success, where high quality iron ore and coal feeds are readily available. This RHF has also been frequently used in the production of direct reduced iron (DRI) from iron and steelmaking by‐products of dust, sludge, and mill scale, but the DRI results in slightly lower metallization and higher gangue material . Pulverized coal is widely available in Australia or China, which is a common by‐product of coal mining process.…”
Section: Introductionmentioning
confidence: 99%